"A Kind of Eloquence of the Body": Quintilian's Advice on Delivery for the Twenty-First-Century Rhetor. Issue 2 (3rd May 2016) - McClish, Glen
ABSTRACT: This essay makes the case that the account of delivery featured in the Institutio Oratoria remains germane to contemporary speech pedagogy. Quintilian emphasizes that (1) powerful delivery is central to eloquent public speaking; (2) delivery functions in concert with the other canons of rhetoric; and (3) delivery is governed by general rhetorical concepts such as decorum and ethos. Furthermore, scrutiny of Quintilian's perspectives on gender and power can lead to fruitful rethinking of current pedagogy's traditionalist tendencies.